Bewijsvoering Analysis of Electronic Evidence in Criminal Cases’s Proving - Aloysius Wisnubroto; Vincentius Patria Setyawan (UNES Law Review, 2023)
An important aspect that cannot be separated from the evidentiary process is related to how to obtain and present evidence to the judge before the trial. Wiretapping as electronic evidence obtained secretly often gives rise to debate from the perspective of bewijsvoering, and the evidentiary value of electronic evidence obtained through wiretapping. This article will discuss the use of wiretapping results as electronic evidence in relation to its evidentiary value in court. The results of this research show that there is a dualism in bewijsvoering the results of wiretapping as electronic evidence, some are of the opinion that bewijsvoering the results of wiretapping as electronic evidence must be obtained legally, and other opinions state that bewijsvoering is a separate matter from proof, as long as the evidence is submitted to the front. the trial is in accordance with the facts and other evidence, then the evidence is considered valid.